Autonomic Parameter and Stress Profile Predict Secondary Ischemic Events After Transient Ischemic Attack or Minor Stroke. Issue 8 (August 2019) - Guan, Ling; Wang, Yongjun; Claydon, Victoria E.; Mazowita, Garey; Wang, Yilong; Brant, Rollin; Collet, Jean-Paul
Abstract : Background and Purpose—: Traditional risk factors for ischemic stroke are body stressors that are related to autonomic autonomic system (ANS) dysfunction. The value of ABCD2 score (age, blood pressure, clinical features, duration of symptoms, diabetes) to predict ischemic stroke after transient ischemic attack is compromised by the inclusion of a limited number of stressors. We aimed to assess whether markers of ANS function and stress could predict the occurrence of secondary ischemic events after transient ischemic attack or minor stroke. Methods—: This is a prospective cohort study in which 201 patients were recruited within 48 hours after initial transient ischemic attack or minor stroke and followed for 90 days to assess the development of secondary ischemic events. ABCD2 score, heart rate variability (HRV) parameters as markers of ANS function, and psychological stress were assessed. Logistic regression and area under the curve (AUC) were used to assess the models' predictive ability. Results—: Morning high frequency (HF) HRV power and changes in HF HRV from morning to afternoon (daytime HF changes) were the most useful HRV predictors for both ischemic events (AUC=0.61 and 0.70) and ischemic stroke (AUC=0.62 and 0.72). Compared with ABCD2 score, 2 HRV-based stress models showed higher predictive ability for ischemic events (AUC=0.82 versus 0.63, 0.76 versus 0.63; P <0.05) and ischemic stroke (AUC=0.87 versus 0.64, 0.82 versus 0.64; P <0.05). Conclusions—: Assessing the effects of stress on the ANS may be an innovative way to stratify the risk of ischemic events after transient ischemic attack or minor stroke. New risk stratification by assessing the dynamic features of ANS dysfunction and stress may help identify high-risk sub-populations that may benefit from added management. Abstract : Supplemental Digital Content is available in the text.